LANGUAGE IMPACT TOWARDS SOCIAL BEHAVIOR OF AT-RISK CHILDREN - Doncheva, Katerina Zlatkova (PUPIL: International Journal of Teaching, Education and Learning, 2019)
Current study examines the use of language towards behavior of at-risk children. At-risk youth living separated from their family are deemed as most vulnerable children with highest risk having high level of anxiety, emotional disorders, aggression and problematic behavior. Children deprived of parental care living across Bulgarian residential homes (N=40) divided into 3 age groups (aged 7-10; aged 11-14; and aged 15-17) participated in 12 experimental activities and has been subjected surveillance of changes in their behavior according to certain use of language and voice (tone). Children adhere to or violate the rules in activities was the main criteria that have been defined for observation. The use of language indicators were divided into certain words with encouraging and reprobation meaning combined with louder or normal voice. ANOVA measures of surveillance assessed the impact of language and speech on behavior of children and indicated significant results for different age groups. The main hypothesis of the survey traces the impact of encouraging words with positive meaning and normal voice for better effect on socially acceptable behavior. Scientifically justified findings of this study indicates existence of a pattern supported the positive impact of language and speech that specialists and teachers can use helping the child absorbing pro-social behavior and gives directions of an effective language-based model of consulting and educating children. The results in current research can help social workers, social educators, teachers and psychologists to find suitable strategy in communication and proper use of language for better results on socialization and adaptation of the child with behavior problems.